If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 8 = 73m Reorder the terms: 8 + X = 73m Solving 8 + X = 73m Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + X = -8 + 73m Combine like terms: 8 + -8 = 0 0 + X = -8 + 73m X = -8 + 73m Simplifying X = -8 + 73m
| 3x(x+5)-5=7+(3+9x) | | 3-24/4=6 | | 13x+45y=17 | | 5.8+x=9.2 | | 3x(x+5)-5=7+(3+3x) | | 7.50t=150.00 | | 5*X-12=28 | | 3*X+7=19 | | x-1+x^2=9 | | 8/12=X | | 5*X=30 | | y-50=-52/3(x-10) | | 6b^2-3b+6=0 | | 2n=-48 | | 17+x=32 | | 15+3/7-7+2*-9 | | x^2=18-x | | S-5/2 | | 2-5/2 | | 2/3(3x+2)=1x | | 27=-3d | | 2/3(3x+3)=1x | | S-5/2=-11 | | 2dicks+9x=8 | | 14/-25 | | 4s=1y | | x=-3+9y | | 150=(m*-30)+300 | | 3(x+8)-7=50 | | 2x^2+16x+2=0 | | -32=x+14 | | 39n^2+18n=0 |